ANALISIS KEBIJAKAN PUBLIK PEMINDAHAN IBU KOTA NEGARA (Jurnal Ekonomi & Kebijakan Publik, 2022)
The government has announced a plan to move the national capital (IKN) to East Kalimantan Province and which has agreed upon at the DPR RI Plenary Meeting in early 2022. There are at least more than six main considerations why moving IKN is important to do. However, these considerations are felt to be insufficient to move the IKN from DKI Jakarta to East Kalimantan. In this regard, this paper will examine and analyze public policy aspects regarding the relocation of the national capital using a qualitative descriptive approach. Therefore, this paper does not only analyze the substance and implementation of policies but also elaborates on the responses from stakeholders. Pros and cons in preparing, building, and relocating the capital, especially in terms of financing/funding and what the economic implications, including potential failure, socio-ecological impact, and lessons learned from several countries. The author classifies the driving factors and inhibiting factors. As a large and important public project, the development and transfer of the IKN has the potential for strategic economic aspects through the realization of an economic transformation and Indonesia-centric, that will give birth to economic diversification and multiplier effects. However, a large economic potential must still consider sociological aspects, geographical aspects, and geopolitical aspects, which must be carried out in anticipation of risks that may arise as a follow up impact.Keywords: national capital city, population density, APBN, economic-socio-cultural-ecological impact and risk anticipationAbstrakPemerintah telah mencanangkan rencana pemindahan ibu kota negara (IKN) ke Provinsi Kalimantan Timur dan telah disepakati dalam Rapat Paripurna DPR RI pada awal Tahun 2022. Setidaknya terdapat lebih dari 6 pertimbangan utama mengapa pemindahan IKN penting untuk dilakukan. Namun pertimbangan tersebut dirasakan belum cukup untuk memindahkan IKN dari DKI Jakarta ke Kalimantan Timur. Berkaitan dengan hal tersebut, tulisan ini akan mengkaji dan menganalisis aspek-aspek kebijakan publik mengenai pemindahan ibu kota negara dengan menggunakan pendekatan deskriptif kualitatif. Oleh karena itu, tulisan ini bukan hanya menganalisis substansi dan implementasi kebijakan saja, tetapi juga mengelaborasi tanggapan dari para pemangku kepentingan. Pro dan kontra dalam persiapan, pembangunan dan pemindahan ibu kota terutama dalam hal pembiayaan/pendanaan serta bagaimana implikasi ekonominya, termasuk potensi kegagalan, dampak sosial-ekologis, dan pembelajaran dari beberapa negara. Penulis mengelompokkan dalam faktor pendorong dan faktor penghambat. Sebagai proyek publik besar dan penting, pembangunan dan pemindahan IKN memiliki potensi aspek ekonomi yang strategis melalui terwujudnya transformasi ekonomi dan Indonesia sentris yang akan melahirkan diversifikasi ekonomi dan multiplier effect. Namun demikian, potensi ekonomi yang besar harus tetap mempertimbangkan aspek sosiologis, aspek geografis, dan aspek geopolitik yang harus dilakukan antisipasi risiko yang mungkin muncul sebagai dampak susulan.Kata kunci: ibu kota negara, kepadatan penduduk, APBN, dampak ekonomi-sosial-budaya-ekologi dan antisipasi risiko